2018
DOI: 10.1093/ckj/sfy083
|View full text |Cite
|
Sign up to set email alerts
|

Impact of introducing electronic acute kidney injury alerts in primary care

Abstract: Background Acute kidney injury (AKI) is associated with decreased survival, future risk of chronic kidney disease and longer hospital stays. Electronic alerts (e-alerts) for AKI have been introduced in the UK in order to facilitate earlier detection and improve management. The aim of this study was to establish if e-alerts in primary care were acted on by examining timing of repeat creatinine testing. Methods The National Health Service England Acute Kidney Injury elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 16 publications
3
25
0
Order By: Relevance
“…Our present data are in line with a similar study in Dundee by Aiyegbusi et al [11]. They found 1,205 AKI episodes in 12 months from an approximate catchment population of 400,000 after introducing an e-alert using the same AKI algorithm.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our present data are in line with a similar study in Dundee by Aiyegbusi et al [11]. They found 1,205 AKI episodes in 12 months from an approximate catchment population of 400,000 after introducing an e-alert using the same AKI algorithm.…”
Section: Discussionsupporting
confidence: 93%
“…Follow-up creatinine was measured within 14 days in 55% of AKI1s, 84% of AKI2s, and 86% of AKI3s, compared to 51, 72, and 77%, respectively in our previous paper [9]. This increase in frequency of repeat creatinine measurements was also mirrored in the Dundee study (from 10 to 59% across all AKI stages) though they looked for repeat sampling by day 7 versus 14 [11]. Holmes et al [12] looked at a population of ∼3 million after the introduction of e-alerts.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have suggested a benefit from using AKI e-alerts on care processes including a reduction in time taken to modify or discontinue medications [ 17 ], and an increase in fluid assessments and prescribing in hospital [ 18 , 19 ]. We have shown in a previous study that the introduction of AKI e-alerts in the community led not only to an increase in creatinine monitoring [ 20 ], but also to higher rates of hospitalization. Several studies have reported reductions in mortality associated with AKI following the introduction of e-alerts [ 21 , 22 ] but have evaluated impact using an uncontrolled before or after comparison, which is at high risk of bias because it does not account for any underlying trend in the data (unlike the ITS analysis used in this study).…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-two studies featured an intervention at the micro (individual patient) level. In 15 the main purpose of the intervention was harm prevention,[13,17,19,21,22,26,28,32,3539] in 12 it was earlier diagnosis,[14,20,24,25,30,31,4045] and in two, risk prediction. [12,46] Harm prevention interventions involved alerts to clinicians of the need to change nephrotoxic drugs (non-prescription, dose altering or drug suspension) based on a patient’s renal function.…”
Section: Resultsmentioning
confidence: 99%
“…[21,24,40,44] Three quarters of these interventions used interruptive alerts,[13,21,38,4346] and in a third the alert was outside the clinicians’ workflow. [21,25,30,31,35,40,44,45] All early diagnosis alerts, apart from one (urine output [25]), were activated by changes in serum creatinine (SCr) levels. This was similar for harm prevention, with a minority of interventions using nephrotoxic drug exposure instead.…”
Section: Resultsmentioning
confidence: 99%